Perforated transverse vaginal septum: a rare case report - Sasikala, Ramaraj; Priyadharshini, Manoharan; Poomalar, G. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
20 year old nulliparous woman married since 1 ½ years attended the gynaecology OPD with history of inability to conceive. She had regular menstrual cycles with normal menstrual flow. Local examination revealed blind vagina with a small opening in the centre. On per rectal examination, uterus was felt and normal in size. Based on history and clinical examination finding, a provisional diagnosis of perforated transverse vaginal septum was made. MRI revealed transverse vaginal septum in the lower 1/3rd of vagina with a small fenestration without haematocolpos or haematometra. Transverse vaginal septum resection was done. Vagina healed well without stricture formation. Transverse vaginal septum in the lower 1/3rd of vagina (perforating type) is a rare entity and hence it is presented.